The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
GMJ 2019
DOI: 10.31661/gmj.v8i0.1350
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics and Treatment of Asthma: A Double-Blinded, Randomized, Placebo-Controlled Clinical Trial

Abstract: Background: We examined the efficiency and safety of a specific synbiotic compound, brand name Kidilact®, in the treatment of asthma in children 12 years of age or younger. Materials and Methods: This double-blinded, randomized, placebo-controlled clinical trial was conducted in Tehran, Iran, from May 22, 2016, to May 21, 2017. One hundred children, 12 years of age or younger, who suffered from mild to moderate asthma were recruited in this study. The subjects were randomly divided into two groups; the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…zinc and fructo-oligosaccharide) asthma management. Multiple outcomes did not show a difference between both groups; the number of outpatient visits, 19 in the synbiotic versus 55 in the control arm ( p = 0.001), was the only statistically significant difference [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…zinc and fructo-oligosaccharide) asthma management. Multiple outcomes did not show a difference between both groups; the number of outpatient visits, 19 in the synbiotic versus 55 in the control arm ( p = 0.001), was the only statistically significant difference [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…A further Iranian RCT investigated the effects of a synbiotic compound containing Bifidobacterium infantis and fructooligosaccharide in school children (12 years of age or younger) with mild to moderate asthma [ 49 ]. The treatment lasted six months.…”
Section: Probiotic Supplementation In Children With Asthma or Wheezin...mentioning
confidence: 99%
“…Another important aspect requires adequate attention: there is evidence that most probiotics fail the primary prevention of asthma [ 78 , 79 ]. Contrariwise, some convincing studies proved that probiotic supplementation reduced asthma severity in children with pre-existing asthma [ 47 , 48 , 49 ].…”
Section: The Relevance Of Propam Study In Asthma Managementmentioning
confidence: 99%
“…As reported by Hassanzad et al [316], no statistically significant clinical outcomes were observed after synbiotics were added to asthma management in a population of Iranian children younger than 12 years.…”
Section: Probiotics Prebiotics and Synbiotics: Prevention And Treatmentmentioning
confidence: 61%
“…Lastly, the roles of probiotics, prebiotics, and synbiotics appear to reduce the respiratory inflammatory pattern via the gut-lung axis, but their role in the prevention and treatment of asthma is questionable due to the connection between the gut and lung microbiomes [303][304][305][306][307][308][309][310][311][312][313][314][315][316]319]. In order to describe the role of dietary supplements (such as fish oil, vitamins, probiotics, prebiotics, and synbiotics) in preventing and improving asthma management in children, further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%